Effectiveness of Boric Acid by Ingestion, But Not by Contact, Against the Common Bed Bug (Hemiptera: Cimicidae) - Sierras, Angela (J Econ Entomol, 2018)
Boric acid has been used as an insecticide in the successful control of agricultural, public health and urban pests long before the advent of synthetic organic pesticides. Boric acid products, formulated as dusts, sprays, granular baits, pastes, gels, and liquids, are widely available to consumers and pest management professionals, especially to control pest infestations within homes. Boric acid dust is commonly used against bed bugs (Cimex lectularius L. [Hemiptera: Cimicidae]), but its efficacy has not been demonstrated. We evaluated the efficacy of boric acid as an ingestible and residual contact insecticide on bed bugs, and compared its efficacy on the German cockroach (Blattella germanica L. [Blattodea: Ectobiidae]) which is known to be susceptible to boric acid by both routes. Dose–response studies of 0–5% boric acid in blood demonstrated that ingested boric acid caused rapid mortality at concentrations of ≥2%, and even 0.5% and 1% boric acid caused 100% mortality, albeit at a slower time course. In contrast, bed bugs survived contact with high concentrations of boric acid dust. Smaller boric acid particles did not increase mortality of either unfed or recently fed bed bugs. The same boric acid products were effective at causing mortality of German cockroaches by both contact and ingestion. We thus conclude that although boric acid is an excellent candidate active ingredient for an ingestible bait formulation, residual applications of dust or spray would be ineffective in bed bug interventions.